Chinese Veterinary Medicine B307 Promotes Cardiac Performance and Skeletal Muscle Contraction via Enhancing Intracellular Calcium Levels and Neural Electrical Activity in Animal and Cell Models. (29th October 2020) - Lien, Chia-Ying; Lu, Chen-Wen; Hsu, Chih-Hsiang; Chuang, Tai-Yuan; Su, Li-Yu; Wu, Wan-Jhen; Jheng, Yong-Sin; Lee, Ming-Chung; Wu, Chung-Hsin
Abstract : The study mainly investigated the effects of Chinese veterinary medicine B307 in cardiac and motor functions in animal models of pigeons and mice. Related cellular mechanisms were also studied in the neuroblastoma cell model of SH-SY5Y. Cardiac functions of pigeons and mice were examined by using moorFLPI Laser color Doppler imager and M-mode echocardiography, and motor functions were examined by using muscle electrical stimulation and force recording in the isolated breast muscle. Intracellular calcium levels and electrical activity of SH-SY5Y cells were examined by using Fura 2-AM fluorescence and MED64 system separately. Our results in vivo found that those pigeons under oral B307 treatment obviously enhanced subcutaneous microcirculation and contractile force and prolonged fatigue time in their breast muscles. Those mice under oral B307 treatment obviously elevated ejection fraction and cardiac output in their hearts. Our results in vitro showed that those SH-SY5Y cells under B307 treatment obviously increased intracellular calcium mobilization and electrical activities. These results revealed that improvement of cardiac and motor functions under B307 treatments may be caused by increasing electrical activities and intracellular calcium levels in neuromuscular cells and a similar mechanism may also occur in muscle cells. Thus, we suggested that B307 can be a functional Chinese veterinary medicine for flying pigeons.